Zero-valent nickel catalyst as well as preparation method and application thereof

By designing a stable layer and a protective layer on the zero-price nickel particles, forming a core-shell structure of 'zero-price nickel particles-stable layer-protective layer', the problem of easy deactivation of the existing zero-price nickel catalyst is solved and the catalyst efficiency is achieved and long-life, suitable for the dechlorination reaction of silicon compounds.

CN119186566AActive Publication Date: 2024-12-27CENT SOUTH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411249846.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-27
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

Existing zero-valent nickel catalysts are prone to deactivate during preparation and use, have poor stability, and are difficult to maintain catalytic activity in air and water, resulting in short life and limited application value.

Method used

The catalyst adopts the core-shell structure of the 'zero-valent nickel particles-stable layer-protective layer'. The stabilizing layer is composed of zero-valent nickel reducing agent. The protective layer is a carbon material or an inorganic oxide. It is designed through surfactant treatment and porous structure to avoid The nickel particles are overly agglomerated and oxidized, enhancing the stability and activity of the catalyst.

Benefits of technology

It significantly improves the structural stability and catalytic activity of the catalyst, extends its service life, enhances its stability and catalytic efficiency in air, and has good application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005031937540000011
    Figure HDA0005031937540000011
Patent Text Reader

Abstract

The invention discloses a zero-valent nickel catalyst as well as a preparation method and application thereof. The zero-valent nickel catalyst comprises zero-valent nickel particles, a stable layer coating the outer surfaces of the zero-valent nickel particles, and a protective layer coating the outer surface of the stable layer, the stable layer comprises any one or two of a reducing metal and a zero-valent nickel reducing agent, and the protective layer comprises any one or more of a carbon material, an inorganic oxide, an organic material and the like. The catalyst disclosed by the invention can keep a stable structure in air, is high in catalytic activity and long in service life, and has a relatively good application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for promoting dechlorination of silicon compounds, and in particular to a zero-valent nickel catalyst and a preparation method and application thereof. Background Art

[0002] The dechlorination process of silicon compounds is an important reaction that can convert chlorine-containing silicon compounds into corresponding dechlorinated products. It can be used to prepare silicon compounds with specific functions, and can reduce or avoid the generation of toxic chlorides, which is more environmentally friendly. The dechlorination reaction of silicon compounds is widely used in organic synthetic chemistry, material science and medicine, especially in the field of semiconductors and chip materials. In the semiconductor industry, the dechlorination reaction of silicon compounds can be used to remove impurities in silicon compounds, improve the purity and crystal quality of silicon materials, and provide high-purity raw materials for chip manufacturing.

[0003] There are many types of catalysts that promote the dechlorination reaction of silicon-based compounds, including precious metal catalysts (such as palladium and platinum), transition metal catalysts (such as nickel, iron, and cobalt), and organic catalysts. Among them, zero-valent nickel catalysts have the advantages of easy access to raw materials, low cost, high catalytic activity, and easy adjustment of structure and properties. However, zero-valent nickel catalysts have a short life and poor stability, and are easily deactivated by factors such as oxidation.

[0004] The Chinese patent application with publication number CN117384210A uses a divalent nickel coordination compound containing a phosphine ligand P(R3)3 and a halogenated hydrocarbon magnesium compound to prepare a zero-valent nickel coordination compound, wherein R3 is selected from alkyl, cycloalkyl, alkenyl, cycloalkenyl, heterocyclic, aryl and heteroaryl. The coordination compound can replace precious metal catalysts to catalyze hydrosilylation reactions, and has high catalytic activity and product selectivity, but does not protect the effective structure of the catalyst.

[0005] The Chinese patent application with publication number CN108854951A uses woody biomass to adsorb water-soluble iron salts and nickel salts, and uses pyrolysis gas as a reducing agent to reduce iron and nickel ions to zero valence, thereby synthesizing a biochar nano zero-valent iron-nickel composite. The composite has low manufacturing cost, strong adsorption performance and reduction degradation ability, and has a significant adsorption and passivation effect on heavy metals, which can be used to purify the environment, but air and water will destroy the valence of iron and nickel. Summary of the invention

[0006] The main purpose of the present invention is to provide a zero-valent nickel catalyst and a preparation method thereof, so as to produce a catalyst with more stable structure and properties and capable of efficiently catalyzing the dechlorination of silicon compounds.

[0007] The present invention also provides an application of a zero-valent nickel catalyst in catalyzing the dechlorination reaction of silicon compounds.

[0008] In order to achieve the above object, according to one aspect of the present invention, a zero-valent nickel catalyst is provided, comprising a zero-valent nickel particle, a stabilizing layer coated on the outer surface of the zero-valent nickel particle, and a protective layer coated on the outer surface of the stabilizing layer;

[0009] The stabilizing layer includes any one or two of a reducing metal and a zero-valent nickel reducing agent, and the protective layer includes any one or more of a carbon material, an inorganic oxide, an organic material, and the like.

[0010] The stabilizing layer is composed of a zero-valent nickel reducing agent with strong reducing properties, which can prevent the deactivation of zero-valent nickel during preparation and use; a zero-valent nickel reducing agent refers to a reducing agent that can reduce a salt containing nickel to zero-valent nickel. The protective layer has a stable structure and a porous structure, which can maintain the activity and structure of the catalyst.

[0011] In one preferred embodiment, the stabilization layer includes any one or two of borohydride, zinc, and manganese.

[0012] In one preferred embodiment, the protective layer includes any one or more of activated carbon, SiO2, Al2O3, polysaccharide, and cellulose. Preferably, the protective layer is activated carbon, and the thickness of the protective layer is 0.5 to 20 nm, preferably 2 to 10 nm.

[0013] In one preferred embodiment, the particle size of the zero-valent nickel particles is 1 to 100 nm, preferably 5 to 50 nm.

[0014] The present invention also provides a method for preparing a zero-valent nickel catalyst, comprising the following steps:

[0015] S1. preparing zero-valent nickel particles;

[0016] S2, immersing the zero-valent nickel particles in S1 in a solution containing a nickel valence stabilizer, filtering, and drying to obtain zero-valent nickel particles coated with a stabilizing layer, wherein the nickel valence stabilizer is any one or more of a reducing metal and a zero-valent nickel reducing agent;

[0017] S3. The surface of the zero-valent nickel particles coated with the stabilizing layer in S2 is coated with a protective agent and dried to obtain the product; the protective agent is any one or more of a carbon material, an inorganic oxide, and an organic material.

[0018] The catalyst containing the core-shell structure of "zero-valent nickel particles-stabilizing layer-protective layer" prepared by the present invention can be used to promote the dechlorination reaction of silicon-based compounds.

[0019] In one preferred embodiment, the protective agent is coated in S3 by any one or more of immersion, coating, and adsorption; preferably, the protective agent is coated in S3 by immersion, and the zero-valent nickel particles coated with the stabilization layer in S2 are immersed in a solvent including the protective agent.

[0020] Impregnation makes the protective layer coating more uniform, and the catalytic efficiency of the obtained catalyst is higher.

[0021] In one preferred embodiment, the immersion times, temperature and time in S3 are 1 to 10 times, 10 to 90° C., and 2 to 48 h, respectively, preferably 2 to 5 times, 40 to 80° C., and 6 to 14 h.

[0022] The above impregnation parameters can ensure that the prepared catalyst has high activity.

[0023] In one preferred embodiment, the method for preparing the zero-valent nickel particles in S1 is to add a zero-valent nickel reducing agent into a solution containing a nickel salt and a surfactant and vigorously stir the solution, and then separate the zero-valent nickel particles from the solution, wash them, and dry them.

[0024] Zero-valent nickel particles can effectively avoid excessive agglomeration and oxidation in air or water under the action of surfactants, thereby increasing the activity of the prepared catalyst.

[0025] In a preferred embodiment, the surfactant is any one or more of acid, ascorbic acid and oleic acid.

[0026] Furthermore, in the preparation method of zero-valent nickel particles in S1, the stirring temperature and time are 5-80° C. and 0.1-24 h, respectively, and preferably 15-35° C. and 0.2-2 h.

[0027] Furthermore, the nickel salt in S1 is any one or more of nickel chloride, nickel sulfate, nickel nitrate, nickel bromide, etc., and the preferred concentration is 0.1 to 2000 g / L, more preferably 10 to 1500 g / L, and further preferably 10 to 500 g / L.

[0028] Furthermore, the concentration of the surfactant in S1 is 5-15 g / L. The solution is a DMF solution, and an ethanol solution is used for washing.

[0029] Furthermore, the zero-valent nickel reducing agent in S1 is preferably sodium borohydride, and the mass concentration of sodium borohydride is 30-70 g / L.

[0030] Furthermore, the drying temperature, atmosphere and time are respectively 100-300° C., inert atmosphere, and 0.5-6 h, preferably 100-150° C., N 2 atmosphere, and 1-3 h.

[0031] Furthermore, the solvent in S2 is any one or more of water, ethanol, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), etc.

[0032] Furthermore, the immersion times, temperature and time in S2 are 1 to 10 times and 10 to 90° C., respectively, and preferably 2 to 5 times and 40 to 80° C.

[0033] Furthermore, the molar mass of the nickel valence stabilizer in S2 is 0.5 to 10 times, preferably 1 to 5 times, the molar mass of the zero-valent nickel particles.

[0034] Further, the protective agent in S3 is one or more of activated carbon, SiO2, Al2O3, polysaccharide, and cellulose. Preferably, S3 is immersed in a solvent including activated carbon, the concentration of the activated carbon is 80-120 g / L, and the solvent is ethanol.

[0035] Furthermore, the structural formula of the silicon compound is SiR1R2R3Cl, wherein R1, R2, and R3 are independently selected from hydrogen groups, halogen groups, organic groups, and the like.

[0036] The present invention also provides the use of the zero-valent nickel catalyst in catalyzing the dechlorination reaction of silicon compounds.

[0037] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0038] The present invention provides a zero-valent nickel catalyst and a preparation method thereof, wherein the catalyst can be used to promote the dechlorination of silicon compounds. Compared with the prior art, the catalyst structure of the present invention is characterized by a "zero-valent nickel particle-stabilization layer-protective layer" core-shell structure. Among them, the zero-valent nickel particles can effectively avoid excessive agglomeration and oxidation in the air or water under the action of a surfactant; the stabilization layer is composed of a nickel-valent stabilizer with strong reducing properties, which can prevent the deactivation of zero-valent nickel during preparation and use; the protective layer has a stable structure and a porous structure, which can maintain the activity and structure of the catalyst. Therefore, the catalyst involved in the present invention can maintain a stable structure in the air, has high catalytic activity, a long service life, and has good application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is the yield of phenylsilane produced by the dechlorination reaction of brominated benzene and monochlorosilane catalyzed by the catalysts in Examples 1 to 17 and Comparative Examples 1 to 4. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.

[0041] In the present invention, unless otherwise specified, all parts and percentages are by weight, and all equipment and raw materials can be purchased from the market or are commonly used in the industry.

[0042] Example 1

[0043] At 25°C, 10g of sodium borohydride was slowly added to a 200mL DMF solution containing 18g of nickel nitrate and 2.5g of ascorbic acid, and the mixture was stirred vigorously for 1h. The zero-valent nickel particles were separated from the solution, washed with an ethanol solution, and dried at 120°C in a N2 atmosphere for 2h. Next, the zero-valent nickel particles were immersed in a 200mL DMF solution containing 5g of sodium borohydride at 60°C for 3 times, and then dried at 120°C in a N2 atmosphere for 2h to coat the particles with a stabilizing layer. Then, the zero-valent nickel particles were immersed in a 100mL ethanol suspension containing 10g of activated carbon powder at 60°C for 10h, and the immersion was repeated 3 times to coat the particles with a protective layer, and then dried at 120°C in a N2 atmosphere for 2h to obtain a stable catalyst having a core-shell structure of "zero-valent nickel particles-stabilizing layer-protective layer". Finally, under the action of the catalyst, benzene bromide and monochlorosilane were reacted at 40°C in a N2 atmosphere for 2 hours, and then the reaction was repeated 10 times using the same catalyst, and the product components after 10 reactions were analyzed by liquid chromatography.

[0044] Example 2

[0045] The difference from Example 1 is that the mass of nickel nitrate is 2 g.

[0046] Example 3

[0047] The difference from Example 1 is that the mass of nickel nitrate is 100 g.

[0048] Example 4

[0049] The difference from Example 1 is that no surfactant ascorbic acid is added.

[0050] Example 5

[0051] The difference from Example 1 is that the method of adding the zero-valent nickel reducing agent is changed from slowly adding 10 g of sodium borohydride to slowly passing 5 g of NH3 gas.

[0052] Example 6

[0053] The difference from Example 1 is that the nickel valence stabilizer is replaced by 8 g of manganese powder instead of 5 g of sodium borohydride.

[0054] Example 7

[0055] The difference from Example 1 is that the nickel valence stabilizer is replaced by 10 g of zinc powder instead of 5 g of sodium borohydride.

[0056] Example 8

[0057] The difference from Example 1 is that the method of coating the protective layer is changed to coating the zero-valent nickel particles three times with 100 mL of ethanol suspension containing 10 g of activated carbon powder.

[0058] Example 9

[0059] The difference from Example 1 is that the method of coating the protective layer is changed to adsorbing the zero-valent nickel particles in 10 g of activated carbon powder three times.

[0060] Example 10

[0061] The difference from Example 1 is that the coating protective layer is nano-silicon dioxide.

[0062] Embodiment 11

[0063] The difference from Example 1 is that the coating protective layer is ethyl cellulose.

[0064] Example 12

[0065] The difference from Example 1 is that the coating protective layer is nano-Al2O3.

[0066] Embodiment 13

[0067] The difference from Example 1 is that the coating protective layer is glucose.

[0068] Embodiment 14

[0069] The difference from Example 1 is that the number of times the coating protective layer is impregnated is once.

[0070] Embodiment 15

[0071] The difference from Example 1 is that the number of times of immersion of the coating protective layer is 10 times.

[0072] Example 16

[0073] The difference from Example 1 is that the immersion time of the coating protective layer is 2 hours.

[0074] Embodiment 17

[0075] The difference from Example 1 is that the immersion time of the coating protective layer is 48 hours.

[0076] Comparative Example 1

[0077] The difference from Example 1 is that when preparing the zero-valent nickel particles, the zero-valent nickel particles are not washed after being separated from the solution, and are not coated with a stabilizing layer.

[0078] Comparative Example 2

[0079] The difference from Example 1 is that anhydrous nickel nitrate is used as a catalyst.

[0080] Comparative Example 3

[0081] The difference from Example 1 is that a commercial zero-valent nickel compound Ni(cod)2 is used as a catalyst, and its chemical structure is as follows.

[0082]

[0083] Comparative Example 4

[0084] The difference from Example 1 is that a di(tri-n-butylphosphine)nickel(0) complex is used as a catalyst, and its chemical structure is as follows.

[0085]

[0086] Liquid chromatography was used to detect the yield of phenylsilane generated by the dechlorination reaction of brominated benzene and monochlorosilane in the above examples, and the yield of phenylsilane was used as a catalyst performance index for comparison. The yield of the reaction products of Examples 1 to 17 and Comparative Examples 1 to 4 was compared. Figure 1 shown.

[0087] From the perspective of the yield of the reaction product, the catalyst stability of the embodiment is better than that of the comparative example. Therefore, the "zero-valent nickel particles-stabilizing layer-protective layer" core-shell structure provided by the present invention can effectively maintain the activity of the catalyst and extend its service life. Among them, the catalyst activity of Examples 1, 3 and 17 is relatively high and the yield within 10 reactions is close, but Example 3 uses more nickel nitrate, which will cause waste, and Example 17 has a longer impregnation time, which is not conducive to the efficient preparation of the catalyst. Therefore, the preparation conditions in Example 1 are more suitable. Comparing Examples 1 and 4, it is found that the yield corresponding to the catalyst without surfactant is only about 62 mol%, because the lack of surfactant will cause zero-valent nickel particles to agglomerate and affect the activity of the catalyst. Comparing Examples 1 and 5, it is found that the yield corresponding to the preparation of the catalyst using NH3 gas as a zero-valent nickel reducing agent is only about 71 mol%, because NH3 is volatile and generates weak bases, and the reduction effect is not as good as sodium borohydride. Comparing Examples 1, 6 and 7, it is found that the yield corresponding to the preparation of the catalyst using manganese or zinc as a nickel valence stabilizer is lower than that of sodium borohydride, and sodium borohydride has a strong ability to protect the zero-valent nickel valence state. Comparing Examples 1, 8 and 9, it is found that the effect of impregnation in the method of coating the protective layer is better. This is because impregnation makes the protective layer coated more evenly. Coating causes the protective layer to be too thick and uneven, and adsorption easily causes the protective layer to be coated loosely. Comparing Examples 1 and 10 to 13, it is better to coat the protective layer with activated carbon. This is because activated carbon has a more developed pore structure, good adsorption, and a high specific surface area, so the prepared catalyst has higher activity. Comparing Examples 1, 14 and 15, it is found that too few or too many impregnation times for preparing the protective layer will affect the activity of the catalyst. Comparing Examples 1, 16 and 17, it is found that the longer the impregnation time, the better the protective layer preparation effect, but considering that the preparation time will also increase the catalyst preparation cost, it is better to control the impregnation time within the range of 6 to 14 hours.

[0088] It should be noted that in this invention, the role of activated carbon as a protective layer is different from that of activated carbon as a catalyst carrier or matrix in other inventions. The role of activated carbon as a protective layer is mainly to protect the catalytic activity of the zero-valent nickel state.

[0089] The applicant declares that the present invention illustrates the detailed method features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method features, that is, it does not mean that the present invention must rely on the above-mentioned detailed method features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0090] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0091] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A zero-valent nickel catalyst, characterized in that It comprises zero-valent nickel particles, a stabilizing layer coated on the outer surface of the zero-valent nickel particles, and a protective layer coated on the outer surface of the stabilizing layer; The stabilizing layer includes any one or two of a reducing metal and a zero-valent nickel reducing agent, and the protective layer includes any one or more of a carbon material, an inorganic oxide, an organic material, and the like.

2. The zero-valent nickel catalyst according to claim 1, characterized in that The stabilizing layer includes any one or two of borohydride, zinc, and manganese.

3. The zero-valent nickel catalyst according to claim 1, characterized in that The protective layer comprises any one or more of activated carbon, SiO2, Al2O3, polysaccharide, and cellulose. Preferably, the protective layer is activated carbon, and the thickness of the protective layer is 0.5 to 20 nm, preferably 2 to 10 nm.

4. The zero-valent nickel catalyst according to claim 1, characterized in that The particle size of the zero-valent nickel particles is 1 to 100 nm, preferably 5 to 50 nm.

5. A method for preparing a zero-valent nickel catalyst, characterized in that The following steps are involved: S1. preparing zero-valent nickel particles; S2, immersing the zero-valent nickel particles in S1 in a solution containing a nickel valence stabilizer, filtering, and drying to obtain zero-valent nickel particles coated with a stabilizing layer, wherein the nickel valence stabilizer is any one or more of a reducing metal and a zero-valent nickel reducing agent; S3. The surface of the zero-valent nickel particles coated with the stabilizing layer in S2 is coated with a protective agent and dried to obtain the product; the protective agent is any one or more of a carbon material, an inorganic oxide, and an organic material.

6. The method for preparing a zero-valent nickel catalyst according to claim 5, characterized in that: The protective agent is coated in S3 by any one or more of immersion, coating, and adsorption. Preferably, the protective agent is coated in S3 by immersion, and the zero-valent nickel particles coated with the stabilization layer in S2 are immersed in a solvent including the protective agent.

7. The method for preparing a zero-valent nickel catalyst according to claim 6, characterized in that: The immersion times, temperature and time in S3 are 1 to 10 times, 10 to 90° C., and 2 to 48 h, respectively, and preferably 2 to 5 times, 40 to 80° C., and 6 to 14 h.

8. The method for preparing a zero-valent nickel catalyst according to claim 5, characterized in that: The preparation method of the zero-valent nickel particles in S1 is to add a zero-valent nickel reducing agent into a solution containing a nickel salt and a surfactant and vigorously stir the solution, separate the zero-valent nickel particles from the solution, and then wash and dry them.

9. The method for preparing a zero-valent nickel catalyst according to claim 8, characterized in that: The surfactant is any one or more of acid, ascorbic acid, oleic acid and the like.

10. Use of the zero-valent nickel catalyst according to any one of claims 1 to 4 or the zero-valent nickel catalyst prepared according to the preparation method according to any one of claims 5 to 9 in catalyzing the dechlorination reaction of silicon compounds.

Citation Information

Patent Citations

  • Zero-valent transition metal, preparation method thereof and removing method for hexavalent uranium ions in aqueous solution

    CN108188410A

  • Preparation method of non-metallic element doped nano zero-valent nickel loaded carbon fiber composite material

    CN108479832A

  • Method for preparing charcoal nanometer zero-valent iron-nickel compound with one-step method

    CN108854951A

  • Carbon-coated transition metal nano composite material as well as preparation method and application thereof

    CN111468118A